Heterogeneous Bubble Nucleation by Homogeneous Crystal Nuclei in Poly(l‐Lactic Acid) Foaming. Issue 4 (7th January 2022) - Longo, Alessandra; Di Maio, Ernesto; Di Lorenzo, Maria Laura
Abstract: A novel method to enhance and control bubble nucleation in poly(l ‐lactic acid) (PLLA) foaming, not relying on external nucleating agents, is presented. Amorphous PLLA is annealed at temperatures close to its glass transition, to allow local alignment of polymer chains in the form of nanosized aggregates, called homogeneous crystal nuclei (HCN). PLLA containing HCN is then foamed after sorption of CO2 at 120 °C and 10 MPa. Under the chosen experimental conditions, HCN can promote growth of PLLA spherulites that can be controlled by thermal‐pressure history. Foam morphology is strongly affected by the presence of HCN, which act as heterogeneous nucleation sites for bubbles. Resulting foams are characterized by a bimodal morphology, with bubbles of about 50–70 µm in diameter developed in the bulk, and much smaller cells of few µm, grown upon pre‐existing crystal aggregates. The method detailed here to attain PLLA foams with tailored morphology can be exploited also for other semicrystalline polymers. Abstract : A novel method to enhance and control bubble nucleation in poly(l ‐lactic acid) (PLLA) foams is presented. Homogeneous crystal nuclei, i.e., nanosized aggregates of a few aligned PLLA chain segments, are demonstrated to promote bubble growth. The foams have a bimodal morphology, with bubbles of 50–70 µm and much smaller cells of few micrometers, which can be further tailored toward nanofoam morphology.